Enhanced Anticancer Activity of Nedaplatin Loaded onto Copper Nanoparticles Synthesized Using Red Algae - Nada Mostafa Aboeita; Sherif Ashraf Fahmy; Mayyada M. H. El-Sayed; Hassan Mohamed El-Said Azzazy; Tamer Shoeib (MDPI AG, 2022)
Marine algae are a rich source of biologically active compounds that can be utilized in various food and pharmaceutical applications. In this study, ultrasound-assisted extraction (UAE) was optimized to maximize yield and total carbohydrate content extracted from the red algae, Pterocladia capillacea. The extract was shown to possess potent antioxidant activity of up to ~70%, and was successfully used as a reducing and capping agent in the green synthesis of copper nanoparticles, which were characterized by UV-spectroscopy, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and dynamic light scattering (DLS). Primarily, CuO nanoparticles with an average size of 62 nm were produced. FTIR spectra for the extract and algal-mediated CuO nanoparticles showed characteristic polysaccharide peaks. The synthesized CuO nanoparticles were subsequently loaded with nedaplatin where UV data suggested a complex formation. Nedaplatin release profiles showed a sustained release that reached a maximum at 120 h. The formulation was shown to have greater cytotoxicity relative to nedaplatin on hepatocellular carcinoma, breast cancer and ovarian cancer cell lines with IC50 values of 0.40 ± 0.08, 1.50 ± 0.12, and 0.70 ± 0.09 µg/mL, respectively. Loading nedaplatin onto CuO nanoparticles synthesized using red algae extract, greatly enhances its anticancer effect.